Pengaruh Profitabilitas, Leverage, dan Kebijakan Dividen Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Sektor Industri Dasar dan Kimia Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Imam Hidayat; Herdiansyah Herdiansyah (STIEM BONGAYA, 2022)
Firm value is an investor's perception of the company, which is often associated with stock prices. The value of the company, which is formed through stock market indicators, is strongly influenced by investment opportunities. Investment spending gives a positive signal from investment to managers about the company's growth in the future, thereby increasing stock prices as an indicator of company value. High stock prices make the value of the company also high (Brealey et al, 2007:46). This study aims to obtain empirical evidence of the effect of Profitability, Leverage, Dividend Policy on Firm Value of basic Industry and Chemical companies listed on the IDX for the period 2018 - 2020. The sampling technique used purposive sampling and obtained 10 companies with a period of 3 years so that 30 were obtained. observed sample. The data analysis model in this study is panel data regression using Eviews 11.0 software. The results showed that profitability (ROA) had an effect on firm value, leverage (DER) had no effect on firm value, and dividend policy (DPR) had an effect on firm value.